2014
DOI: 10.1371/journal.pone.0090959
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Family Support, Depression, and Suicidal Ideation among People Living with HIV/AIDS: A Cross-Sectional Study in the Kathmandu Valley, Nepal

Abstract: BackgroundDepression and suicidal thinking occur frequently alongside HIV/AIDS, triggering profound detrimental impacts on quality of life, treatment adherence, disease progression, and mortality. Yet the psychosocial factors contributing to these psychiatric comorbidities remain underexplored, particularly in the developing country context. This study thus examined different dimensions of perceived family support in relation to depression and suicidal ideation among people living with HIV/AIDS (PLWHA) in Nepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
2
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 41 publications
8
69
2
10
Order By: Relevance
“…MDD among HIV population was associated with family history of affective disorder, alcohol dependency disorder, and female gender. 9 Similar to previous studies 11,12 our study showed that majority (n=36, 36.4%) belonged to age group 30-39 yrs. In our study, the males (n=49, 49.5%) and the females (n=50, 50.5%) were almost equal in number, which can be counted for one of the strengths of the study.…”
Section: Demographysupporting
confidence: 90%
See 1 more Smart Citation
“…MDD among HIV population was associated with family history of affective disorder, alcohol dependency disorder, and female gender. 9 Similar to previous studies 11,12 our study showed that majority (n=36, 36.4%) belonged to age group 30-39 yrs. In our study, the males (n=49, 49.5%) and the females (n=50, 50.5%) were almost equal in number, which can be counted for one of the strengths of the study.…”
Section: Demographysupporting
confidence: 90%
“…A community based crosssectional study of 322 adult PLWHA in the Kathmandu valley, reported 25.5% to have BDIdefined depression. 9 An specialty HIV clinic at a tertiary care centre of South India reported syndromal depression in 40 percent of seropositive individuals. Severity of depressive symptoms was related to abuse or dependence on alcohol (47%), and poor social support (43%) 8 This study was an attempt to study depression in PLWHA under ART in an out-patient clinic in TUTH, a tertiary centre hospital of this country located in the capital city, Kathmandu.…”
Section: Introductionmentioning
confidence: 99%
“…Family support is one of the most important forms of social support for people in situations of vulnerability, being an important protective factor for the development of psychosocial disorders such as depressive symptoms and suicidal thoughts. (7,12) When the family environment is insufficient, or unable to meet their demands, PLWHA sought support in society in general, represented here as a network of individuals and institutions that had no family relationship with the participants. The participants' statements, and the way the words be-haved in the classes, point to a situation of helplessness, in which individuals do not have social or emotional support.…”
Section: Discussionmentioning
confidence: 99%
“…Another characteristic of the study participants was being older (<50), which makes them more likely to have less social support and develop mental health problems. (12,14) The perception by PLWHA of health services as an obstacle to their quality of life is an alarming finding. The constant procedures, considered routine for professionals, become symbolic and representative images of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The study procedures have been reported in detail elsewhere (50)(51)(52)(53)(54)(55)(56). In brief, HIVinfected persons were recruited through the network of five non-government organizations (NGOs) working with HIV-infected persons in the Kathmandu Valley.…”
Section: Study Design and Settingmentioning
confidence: 99%